A narrative review of trends and challenges of substance use in Punjab: a 10-year analysis of data from 2015 to 2024 - Heena Sachdeva; Manish Sharma; Maninder (Discover Public Health)
Abstract Background Punjab, a northwestern state of India, is experiencing a serious substance use crisis with wide-ranging public health, social, and economic consequences. Methods This narrative review examines secondary data from official reports, government records, and public health databases from 2015 to 2024 to assess trends in substance use, key contributing factors, and institutional responses. Results Analysis revealed over 51,000 NDPS cases and the seizure of more than 4,600 kg of heroin between 2015 and 2024. A population survey indicated that 15.4% of residents reported substance use in 2022. Historical data shows that over 230,000 people were opioid-dependent in Punjab as early as 2015. Contributing factors include youth unemployment, poor mental health infrastructure, and proximity to international drug trade routes. Despite intensified enforcement, public health responses remain inadequate. For instance, many de-addiction centers are under-resourced and lack standardized treatment protocols. Conclusion Addressing Punjab’s substance use crisis requires a multisectoral approach that combines law enforcement with robust mental health and rehabilitation services. School-based prevention, vocational training, and stigma reduction are essential for sustainable impact.